Pengaruh Adopsi Fintech dan Literasi Keuangan terhadap Kinerja Keuangan dengan Kepercayaan Digital sebagai Variabel Moderasi pada Bank Syariah - Pamikatsih, Mutia Pamikatsih; Cahyaningsih, Regita Cahyaningsih (ICON Publisher, 2025)
This study investigates the influence of Fintech Adoption and Financial Literacy on the Financial Performance of Islamic banks in Indonesia, with Digital Trust examined as a moderating variable. Utilizing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 150 managerial respondents across 14 Islamic commercial banks. The findings reveal that Fintech Adoption significantly and positively affects Financial Performance (p < 0.05), highlighting the strategic importance of digital transformation in the banking sector. However, Financial Literacy does not demonstrate a significant impact, nor does Digital Trust significantly moderate either the Fintech Adoption–Performance or Financial Literacy–Performance relationships. These results suggest that organizational-level factors and system integration may play a more decisive role than individual competencies or perceived trust in shaping performance outcomes. Theoretically, this research reinforces the Technology-Organization-Environment (TOE) framework while challenging assumptions from Human Capital and Trust-Based Models. The study’s practical implication emphasizes prioritizing digital infrastructure development over isolated staff training in Islamic banking. Limitations include its cross-sectional design and institutional focus, prompting future research to adopt multi-level and longitudinal approaches. This study contributes to the growing discourse on digital finance within faith-based financial institutions.